TYPES OF DEIXIS IN THE SONG LYRICS OF MAROON 5’S RED PILL BLUES ALBUM - Lusiana, Ni Kadek Elva; Juniartha, I Wayan; Maharani, Putu Devi (Journal of Language and Applied Linguistics, 2021)
This research entitled An Analysis of Person Deixis of Maroon 5’s Red Pill Blues Album. Deixis is an expression in language that used to point who, where, and when that depend on the context. The objectives in this research are 1). to find out and identify types of deixis in the song lyrics of Maroon 5’s Red Pill Blues Album 2). to analyze context of deixis in the song lyrics of Maroon 5’s Red Pill Blues Album. Documentation method is used in collected the data using listening, reading and note taking techniques. Qualitative method is used to analyze the data by using descriptive word for explaining the data. The result of this research shows that all types of deixis found in the song lyrics of Maroon 5’s Red Pill Blues album which are person deixis, spatial deixis, temporal deixis, social deixis and discourse deixis.. This research found that there are 321 data found of person deixis with percentage of 69%, 95 data found of temporal deixis with percentage of 20.3%, 28 data found of discourse deixis with percentage of 5.9%, 16 data found of spatial deixis with percentage of 3.4% and 7 data found of social deixis with percentage of 1.4%.